2016
DOI: 10.1111/cns.12504
|View full text |Cite
|
Sign up to set email alerts
|

The Neural Basis of Postural Instability Gait Disorder Subtype of Parkinson's Disease: A PET and fMRI Study

Abstract: The involvement of the caudate, FG, and prefrontal-parietal network may be associated with the prominent gait impairments of PIGD subtype. Our findings expand the pathophysiological knowledge of PIGD subtype and provide valuable information for potential neuromodulation therapies alleviating gait disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 43 publications
(43 reference statements)
0
23
0
2
Order By: Relevance
“…Alterations in this brain area would impair the predictability of body orientation and the maintenance of certain relative positions of the body segments, thus directly impairing the balance control . A predominant involvement of the left parietal cortex in gait was also shown in other brain imaging studies with resting state or imaged locomotion protocols . A hypofunctioning left parietal cortex would also lead to downregulation of the activity in the primary motor cortex and supplementary motor area, delaying the adaptation of gait to environmental needs, and additionally increasing the risk of falls in parkinsonian patients.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Alterations in this brain area would impair the predictability of body orientation and the maintenance of certain relative positions of the body segments, thus directly impairing the balance control . A predominant involvement of the left parietal cortex in gait was also shown in other brain imaging studies with resting state or imaged locomotion protocols . A hypofunctioning left parietal cortex would also lead to downregulation of the activity in the primary motor cortex and supplementary motor area, delaying the adaptation of gait to environmental needs, and additionally increasing the risk of falls in parkinsonian patients.…”
Section: Discussionmentioning
confidence: 87%
“…Late recognition of patients at risk of falls prevents their timely treatment and is mainly related to the unclear pathophysiology of balance dysfunction in PD. While nigrostriatal dopaminergic denervation does not differ between the PD patients with and without falls, functional brain imaging studies has recently showed a direct involvement of cortical areas in PD fallers . Brain metabolic imaging with 2‐deoxy‐2‐[18F]fluoro‐D‐glucose ([18F]DG) and positron emission tomography (PET) can reliably identify the symptom‐specific brain metabolic changes for tracking the progression of neurodegenerative processes and their response to treatment .…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, patients with a tremor-dominant phenotype rarely develop dementia. Zhang et al found additional hypometabolism in the caudate nucleus and inferior parietal lobule in patients with postural instability gait disorder compared with tremordominant patients (22). Decreased metabolism in parietaloccipital regions was found in PD patients with RBD compared with PD patients without RBD (23).…”
Section: Pd and Cognitive Impairmentmentioning
confidence: 98%
“…Postural control is referred to the control of the body’s position with the aim of maintenance of balance and orientation3334. A previous study showed that more cognition-related regions, such as caudate, fusiform gyrus and inferior parietal lobes35, were affected in PIGD patients. One study reported that cognitive performance was a predictor of postural control in individuals with PD36.…”
Section: Discussionmentioning
confidence: 99%
“…Reduced serotonergic neurotransmission impaired learning and memory function, whereas an increased serotonergic neurotransmission was associated with an improved cognitive and behavioral performance, not only in rodents, but also in AD patients45. A recent functional Magnetic Resonance Imaging (MRI) study demonstrated that the dysfunction of prefrontal-parietal network might be associated with the prominent gait impairments of PIGD subtype35. 5-HT projections originating from the raphe nuclei converged at several key target structures involved in memory, ascended within the medial forebrain bundle and were projected to prefrontal cortex45.…”
Section: Discussionmentioning
confidence: 99%